Constitutional foundations of the Independent State of Croatia - Zdravković Miloš (Anali Pravnog Fakulteta u Beogradu)
When the Independent State of Croatia (NDH) was formed, in the head of that state came so-called the Ustashe movement. The paper shows that in the period from 1941 until 1943 the NDH had required elements of statehood. The organization of the state authorities was made according to the model of the Ustashe organization with the title Poglavnik (Leader) in the head of the state who had all the dictatorial powers. The efficiency of the state authorities, but also necessary support of the enough number of population proves that the NDH had a constitution in its material sense, although the constitution was never brought. The foundations of the functioning of NDH were determined by uncodified constitution which was made of: The Ustashe Constitution (1929), The Principles of the Ustashe Movement (1933) and certain legislations of the constitutional significance which were adopted after the NDH was formed.